Medical management and perioperative issues in pediatric pheochromocytoma - A case report with review of literature - Naresh Lal; Ankur Ohri; Vibin kumar Vasudevan; Rachna Sharma; Praveen Khilnani (Wolters Kluwer Medknow Publications, 2017)
Pheochromocytoma is a tumor arising out of embryological neural crest, being a tumor of adrenal medulla secreting predominantly norepinephrine as well as epinephrine(about 20% cases) leading to frequent surges of vasopressor catecholamines leading to systemic hypertension, hypertensive emergencies and associated cardiac, neurological, and renal sequalae. Though somewhat rare in pediatric age group, it remains an important etiological factor to think about when there is intractable hypertension or rapid swings of blood pressures leading to headaches and palpitations with family history of hypertension or as a part of familial endocrine neoplasia. Treatment remains laproscopic or open surgical resection under general anesthesia, however perioperative care remains a challenge for the anesthesiologist, intensivist requiring adequate medical control of hypertension with alpha blockers such as phenoxybenza- mine before undertaking anesthetic induction and important monitoring measures instituted during intraoperative and postoperative period for close monitoring of blood pressure and intravascular volume status as well as hemodynamics. We review a case report with literature review regarding perioperative management of pheochromocytoma.